Self-Regulated Learning in the Age of GenAI How Undergraduate EFL Students Engage with Chat-Based AI in Essay Writing - Rifqah (Indonesian Journal Publisher, 2026)
This study explores how undergraduate EFL students use chat-based AI tools in essay writing through the lens of Self-Regulated Learning (SRL), focusing on the forethought, performance, and self-reflection phases. A qualitative research design was used, and data were collected through semi-structured interviews with 12 English Education students selected through purposive sampling based on their experience using chat-based AI tools. The data were analyzed using thematic analysis with both deductive and inductive coding. The findings show that in the forethought phase, students mainly set simple goals such as completing essays quickly, getting good grades, and meeting academic requirements. They also used AI to help generate ideas and organize essay structure when they had difficulties. In the performance phase, students used chat-based AI for brainstorming ideas, improving grammar and vocabulary, and developing their writing. However, they did not fully depend on AI output and often rewrote and checked the content to maintain originality and clarity. In the self-reflection phase, students viewed AI as helpful for improving writing speed, ideas, and language quality, but they also expressed concerns about overuse and dependence. Despite this, most students reported improvements in their writing skills and planned to continue using AI carefully. The study concludes that chat-based AI supports students in essay writing, but its effectiveness depends on how students regulate its use across SRL phases. The findings show that students are starting to apply self-regulated learning strategies, although their writing is still strongly influenced by task completion goals and academic demands.